A Review on the Bacterial Concrete Properties. Issue 1 (November 2020) - Jena, Shradha; Basa, Bidyadhar; Chandra Panda, Kishor
Abstract: A very commonly used and widespread building material, concrete has various limits of using it, one of which is crack formation. Formation of larger cracks let water and CO2 enter into the building materials which in turn react along with other chemicals causing an eye catching reduction in strength and durability. If immediate remedies are not taken to heal the cracks, it might lead to more serious problems like bigger cracks, more leakage of water, reduced strength, costlier to repair. Hence the best way to deal with such situation and to heal concrete even before it starts spreading is self-healing concrete. Self-healing concrete is the most recent and most current cutting-edge technological development in the field of building materials. Self-healing bacteria has the capacity to heal itself. The underlying principle of this mechanism is forming calcium carbonate precipitate with the help of bacteria as a blocking material for cracks. This new and innovative introduction of bacteria into the building materials show new light on production of sustainable, durable, strong concrete having prolonged life period. Due to the introduction of bacteria in concrete, the name becomes bacterial concrete. Bacterial / microbial concrete is pollution free, economic and cost effective. This paper aims at defining bacterial concrete, mechanism and its effects on concrete properties.